2015
DOI: 10.1016/j.ijscr.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic UCLA for single tilted implant in an aesthetic region

Abstract: HighlightsThis study investigated the aesthetic of the prosthesis rehabilitation.Patient satisfaction after rehabilitation.Importance of radiographic control case report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…UCLA [68][69][70][71] type of abutment directly attaches to the implant and provide a pattern for fabrication of screw retained restoration [6]. They are indicated in single implants, in limited interocclusal space, or in cases of tilted implants.…”
Section: The Cast Goldmentioning
confidence: 99%
“…UCLA [68][69][70][71] type of abutment directly attaches to the implant and provide a pattern for fabrication of screw retained restoration [6]. They are indicated in single implants, in limited interocclusal space, or in cases of tilted implants.…”
Section: The Cast Goldmentioning
confidence: 99%
“…Initially this component was made to fit the external hexagonal platform (EH), and now is available for internal hexagonal IH and internal connection (IC). UCLA is widely used to promote treatment agility and cost reduction (Goiato et al, 2015). Studies have reported that the use of UCLA castable abutments presents distortions which compromise the accurate fit at the IAI (Abduo, 2014; de decreases below a critical level, the stability of the screw joint will be compromised (Gupta et al, 2015).…”
Section: Introductionmentioning
confidence: 99%